Persepsi Ibu Balita Terhadap Pertumbuhan dan Perkembangan Balita Mothers Perceptions of Toddler Growth and Development - Anik Kurniawati; Rohmi Handayani (Rena Cipta Mandiri, 2025)
Toddler growth and development is a crucial phase that determines the quality of an individual's life in the future. During this period, children experience rapid physical, cognitive, emotional, and social development. Parents play a central role in directing and supporting this process through parenting, stimulation, and their understanding of their child's growth and development needs. Parents' perceptions of toddler growth and development greatly influence the way they care for and educate their children. The purpose of this study was to determine the characteristics of respondents and people's perceptions of toddler growth and development. This study used a quantitative descriptive design conducted in Glodogan Village, South Klaten District, Klaten with 39 respondents. The sampling technique used was accidental sampling. The results showed that all respondents (100%) had positive perceptions of toddler growth and development. The characteristics of the respondents were mostly (90%) in the healthy reproductive age range, 44% of respondents with secondary education and 46% of respondents were housewives.